divide the following
Attachments:
![](https://hi-static.z-dn.net/files/dc8/571c25e443fbb81f937f218120701224.jpg)
Answers
Answered by
0
Answer:
6) (3x+2) (5x-3)
Step-by-step explanation:
6) = 15x^2+x-6
= 5x (3x+2). -3 (3x+2)
= 15x^2+10x-9x-6
= 5x (3x+2)-3 (3x+2)
= (3x+2) (5x-3)
Answered by
0
Answer:
Step-by-step explanation:
4. x² - 4 =(x + 2)(x - 2)
(x² - 4) ÷ (x + 2) = x - 2
10. a³ + b³ = (a + b)(a² - ab + b²)
x³ + 1 = (x + 1)(x² - x + 1)
(x³ + 1) ÷ (x + 1) = x² - x + 1
For (12) and (14) see attachment.
Attachments:
![](https://hi-static.z-dn.net/files/d19/470123c1b4e789c270b8a9557526e511.jpg)
Similar questions